Nematodes as Drivers of Plant Performance in Natural Systems. (March 2021) - Wilschut, Rutger A.; Geisen, Stefan
Abstract : Nematodes form an important part of soil biodiversity as the most abundant and functionally diverse animals affecting plant performance. Most studies on plant–nematode interactions are focused on agriculture, while plant–nematode interactions in nature are less known. Here we highlight that nematodes can contribute to vegetation dynamics through direct negative effects on plants, and indirect positive effects through top–down predation on plant-associated organisms. Global change alters these interactions, of which better understanding is rapidly needed to better predict functional consequences. By expanding the knowledge of plant–nematode interactions in natural systems, an increase in basic understanding of key ecological topics such as plant–soil interactions and plant invasion dynamics will be obtained, while also increasing the insights and potential biotic repertoire to be applicable in sustainable plant management. Highlights: The impact of soil nematodes -the most abundant animals on Earth- on plant performance have mostly been studied in agricultural systems and are only partly understood in natural systems. There is accumulating evidence that nematodes affect natural plant performance by contributing to negative plant–soil feedbacks, altering rhizosphere microbial communities and enhancing nutrient cycling. Molecular methods will further increase this understanding, especially by elucidating species specificity and underlying molecular mechanisms of plant–nematode interactions. Increased knowledge is needed to understand how changes in nematode community structure, which are imposed by several global change drivers, feed back to plant performance and plant community composition.